The Role of Dance Studios as a Medium for Preserving Traditional Arts in the Era of Modernization - Diwani Elfarisyah; Juliani; Dewi Agustin; Imelda Ariska; Sintia (Yayasan Zia Salsabila, 2025)
This study aims to explore the role of dance studios (sanggar tari) in preserving traditional arts amid the challenges of modernization. Using a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews, and document analysis. The findings indicate that traditional arts possess aesthetic value, spirituality, and play a significant social role in shaping cultural identity. However, modernization presents major challenges such as shifting values, identity crises among the younger generation, and the dominance of popular culture. In this context, dance studios serve as non-formal educational institutions that not only teach technical skills but also instill values of character, tolerance, and social responsibility. The studios act as cultural preservation centers by fostering youth, organizing performances, collaborating with the government, and innovating learning methods. Measures such as integrating traditional dance into local curricula, utilizing digital media, and government support are key factors in the successful preservation of traditional arts. Dance studios also provide inclusive spaces that promote intercultural social interaction while strengthening community bonds. Thus, dance studios hold great potential as agents of traditional art preservation and character building in the era of globalization. This study recommends increased and integrated support to ensure the sustainability of studios as guardians of local culture amidst the currents of modernization.